Survival : global politics and strategy. February-March 2025, (the International Institute for Strategic Studies, 2021)
Survival, the IISS's bimonthly journal, challenges conventional wisdom and brings fresh, often controversial, perspectives on strategic issues of the moment. In this issue: · François Heisbourg considers the ramifications for Europe of the United States' potential withdrawal of support for Ukraine · Victor Duenow assesses the effects of Finland's and Sweden's NATO membership on the Alliance's posture and options in the Baltic Sea · Evan A. Laksmana considers the wider implications of increased cooperation between China and Indonesia · Jonathan Stevenson explores how the Republic of Ireland's membership in NATO could safeguard the Good Friday Agreement and enhance European security · And nine more thought-provoking pieces, as well as our regular Book Reviews and Noteworthy column. To read free articles from the journal, please visit its homepage at https://www.tandfonline.com/journals/tsur20. Editor: Dr Dana Allin Managing Editor: Jonathan Stevenson Associate Editor: Carolyn West Editorial Assistant: Anna Gallagher
Keywords: Strategy.; Military policy.; Disarmament.; elektronické knihy; electronic books